Assessing Longitudinal Relationships between Financial Performance and Downsizing. Issue 8 (20th August 2014) - Chhinzer, Nita N; Currie, Elliott
Abstract : Purpose: We suggest that divergent financial performance triggers different rationales for the decision to downsize (excuses, justifications, apologies or denials) and that organizational financial performance post-downsizing varies based on the initial downsizing rationale. Design/methodology/approach: A mixed methods approach paired content analysis of 178 downsizing announcements from 2005-2011 with organizational financial data pre and post-downsizing event. Paired sample t-tests determined mean differences in organizational financial performance pre and post-downsizing based on six commonly used organizational performance measures (accounting and human resources metrics). Longitudinal performance trends were evaluated using event history analysis. Findings: Organizational experiencing both financial growth and decline engage in downsizing, but organizational financial performance varies based on downsizing rationale. For example, organizations engaging in excuse based downsizing experienced significant levels of volatility and decline pre-downsizing, but growth post-downsizing. However, organizations engaging in justification based downsizing experienced financial decline pre-downsizing, but no significant additional decline post-downsizing. Research limitations/implications: Collection of information over multiple business or economic cycles, or categorizing organizations based on industry, organizations size or number of employees may provide additional information on the relationship between downsizing and organizational financial performance. Practical implications: Organizational performance pre and post-downsizing varies based on downsizing rationale. Additionally, metrics used to evaluate downsizing success or failure should be considered carefully. Originality/value: We help explain divergent results in existing research on the relationship between downsizing and organizational financial performance by identifying downsizing as a multi-dimensional event. Our study indicates that organizational experience both financial growth and decline engage in downsizing, but rationalize the downsizing differently (according to social accounts).